Identification of amino acids involved in histamine potentiation of GABAA receptors - Thiel, Ulrike; Platt, Sarah J.; Wolf, Steffen; Hatt, Hanns; Gisselmann, Günter (Frontiers in Pharmacology, 2015)
Histamine is a neurotransmitter involved in a number of physiological and neuronal functions. In mammals, such as humans and rodents, the histaminergic neurons found in the tuberomamillary nucleus (TMN) project widely throughout the central nervous system (CNS). Histamine acts as positive modulator of GABA(A) receptors (GABA(A)Rs) and, in high concentrations (10 mM), as negative modulator of the strychnine-sensitive glycine receptor. However, the exact molecular mechanisms by which histamine acts on GABA(A)Rs are unknown. In our study, we aimed to identify amino acids potentially involved in the modulatory effect of histamine on GABA(A)Rs. We expressed GABA(A)Rs with 12 different point mutations in Xenopus laevis oocytes and characterized the effect of histamine on GABA-induced currents using the two-electrode voltage clamp technique. Our data demonstrate that the amino acid residues ß2(N265) and ß2(M286), which are important for modulation by propofol, are not involved in the action of histamine. However, we found that histamine modulation is dependent on the amino acid residues alpha1(R120), ß2(Y157), ß3(D163), ß3(V175) and ß3(Q185). We showed that the amino acid residues ß2(Y157) and ß3(Q185) mediate the positive modulatory effect of histamine on GABA-induced currents, whereas alpha1(R120) and ß2(D163) form a potential histamine interaction site in GABA(A)Rs.